PENGARUH JENIS KEMASAN DAN WAKTU PENYIMPANAN PADA PAKAN BROILER STARTER TERHADAP KADAR AIR DAN PROTEIN KASAR - Bondan Dwinarto; Devi Haryanti; Suratmin Utomo (Universitas Muhammadiyah Jakarta, 2018)
Feed storage and packaging will be effected the quality of phisical, chemist and microbiology. Packaging are one of methode for protecting quality from damage of environment. This research to determine the effect of packaging type and storage time for broiler starter feed. This research using methode statistical Complete Randomized Desing Factorial (5x7) with three replications. The fixed variable in his research are Broiler Starter Feed. The first independent variable is the type of packaging (glass bottle, plastic bottle, aluminum foil vacuum plastic, vacuum plastic, and plastic seal) and the second independent variable is storage (14, 169, 338, 506, 674, 842, 1010 hours). The dependent variables were research are water content test with using methode SNI.01-2891-1992 and Crude Protein testing with kjeldahl methode using AOAC 2005, Chapter 4 Item 4.2.11. method 2001.11. Analysis data by using comparison of graphic regression. The maximum results showed that aluminum foil vacuum plastic container with water content of 10,8137% and crude protein 22,4661% at 842 hours storage (± 5 weeks), water content regression are y = 0.0003x + 10,636 with R2 = 0,9085 and crude protein regression y = 0,0007x + 23,07 with R2 = 0,9477. All test results with various packaging methods and storage time conducted in this study are still in accordance with the standard of feed starter broiler SNI 8173.2.2015 with a maximum water content of 14% and crude protein at least 20%.